TIC´s y educación en ciencias naturales - Suntasig Marín, Irena Mariela (2016)
The application of diagnosis allowed to identify the lack of techniques and instruments of assessment in the area of Natural Sciences at the moment of developing and applying them, it results a monotonous work due to the student has been doing it progressively without using the technological tools, for this reason, the objective is to implement an interactive assessment model that is supported on TIC´s to solve the lack of techniques and instruments in the process of assessing the learning of students of the fifth year of general basic education at “Dr. Néstor Mogollón López” school, using instruments of investigation such as the interview and surveys so obtaining diagnostic results of the research problem which generates a huge impact, strengthening the attitude of students and teachers in the use and application of TIC´s and Education, by including new models of interactive evaluations, motivation to learn and manipulate technological tools in students’ training process, being directly benefited the educational community, since students of the fourth year to students of the seventh year of general basic education and indirectly the other years of basic education who constitute the school so, the image of the institution in the sector.